Evolution of the porous structure for phosphoric acid etching carbon as cathodes in Li–O2 batteries: Pyrolysis temperature‐induced characteristics changes - Feiyang Yang; Ying Yao; Yunkai Xu; Cong Wang; Meiling Wang; Jingjie Ren; Cunzhong Zhang; Feng Wu; Jun Lu (Carbon Energy, 2024)
Abstract Although biomass‐derived carbon (biochar) has been widely used in the energy field, the relation between the carbonization condition and the physical/chemical property of the product remains elusive. Here, we revealed the carbonization condition's effect on the morphology, surface property, and electrochemical performance of the obtained carbon. An open slit pore structure with shower‐puff‐like nanoparticles can be obtained by finely tuning the carbonization temperature, and its unique pore structure and surface properties enable the Li–O2 battery with cycling longevity (221 cycles with 99.8% Coulombic efficiency at 0.2 mA cm−2 and controlled discharge–charge depths of 500 mAh g−1) and high capacity (16,334 mAh g−1 at 0.02 mA cm−2). This work provides a greater understanding of the mechanism of the biochar carbonization procedure under various pyrolysis conditions, paving the way for future study of energy storage devices.